Influential predictors for financial adequacy among Malaysian public sector employees - Abdul Rahim @ Abdul Wahab, Husniyah; Othman, Mohd Amim; Sabri, Mohamad Fazli; Md Jusoh, Zuroni (Australian Academy of Business and Social Sciences, 2015)
Financially well employees are presumed to be portraying good work attitude and may result in good work performance. This will benefit their employer and organization. Knowing the adequateness level of their finances and what influence it is important as it will also affect the organization. Hence, this study was performed to identify influential factors predicting financial adequacy among public sector employees. A cross-sectional study using a multistage random sampling was employed. Self-administered questionnaires were distributed at the work-place of public sector employees in Peninsula Malaysia and were able to obtain 472 usable questionnaires. Logistic regression analysis controlled for socioeconomic characteristics identified savings ratio as the most influential predictor for financial adequacy followed by number of insurance policy and net-worth. The likelihood of an employee to be financially adequate by these redictors was from four to five times as compared to being financially inadequate. Furthermore, financial risk management knowledge was also determined as influential predictor for financial adequacy. The results suggests for a financial education at the work-place to educate the employees on the need to increase savings, purchase various insurance policies and having a positive net-worth to increase employees’ financial well-being for the sake of the organization’s success.